Rasch analysis in developing Jambi culture-based ethnomathematics test for prospective mathematics teachers - Ramalisa, Yelli; Falani, Ilham; Pasaribu, Feri Tiona (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Teachers have an important role in the successful implementation of ethnomathematics in the classroom. Teachers need to have a comprehensive understanding of the context of ethnomathematics. This study aims to develop an instrument for measuring prospective teachers' ethnomathematics knowledge. The instrument was developed in the context of Jambi culture. This research is development research using the Plomp Model, which consists of three stages, namely: 1) preliminary research stage, 2) prototyping stage, and 3) assessment stage. The instrument developed consists of seven indicators and 43 items. Five experts in the fields of cultural studies and mathematics education carried out the instrument validation. The instrument was tested on 74 prospective mathematics teachers. The results show the instrument for measuring ethnomathematics knowledge of prospective mathematics teachers that was developed meets the criteria of unidimensionality, validity & reliability and does not indicate item bias. Therefore, this instrument is appropriate for use in measuring the ethnomathematics knowledge of prospective mathematics teachers in the Jambi cultural context.